The effect of bee pollen on bone biomechanical strength and trabecular bone histomorphometry in tibia of young Japanese quail (Coturnix japonica). - Ewa Tomaszewska; Sebastian Knaga; Piotr Dobrowolski; Krzysztof Lamorski; Mirosław Jabłoński; Agnieszka Tomczyk-Warunek; Mohammed Jard Kadhim; Monika Hułas-Stasiak; Grzegorz Borsuk; Siemowit Muszyński (PLoS ONE, 2020)
It has been demonstrated in numerous studies that bee pollen supplementation shows numerous positive effects on health. However, its impact on bones is largely unknown. The purpose of this study was to investigate the effect of bee pollen supplementation on the tibia biomechanical properties and bone morphometric measures using Japanese quail as an animal model. The experiment was arranged in a 2x2x2 factorial design, with sex, quail line (meat-type or egg-lying type), and bee pollen inclusion (0 or 10 g/kg of feed) as factors. The quails were one-day-old at the beginning of the experiment, they were euthanized after 42 days. Our study showed for the first time unfavorable effects of bee pollen on bones properties. Bee pollen supplementation negatively affected bone structure, irrespective of quails' sex or line type. Bone length (P < 0.001), weight (P < 0.01), and mean relative wall thickness (P < 0.01) and mineralization (P < 0.05) were reduced by bee pollen treatment. For female quails, irrespective of line type, the decrease of yield load (P < 0.001), ultimate load (P < 0.01), yield stress (P < 0.001) and ultimate stress (P < 0.05) was noted. Analysis of growth plate in bone metaphysis showed that bee pollen supplementation slowed the process of bone maturation irrespective of sex (P < 0.05). On contrary, dietary bee pollen positively affected bone homeostasis of trabecular bone in bone metaphysis as bone mineral density increased in experimental groups (P < 0.05). In males, this was the result of the increase of trabecular thickness (P < 0.01), in females due to the reduction of trabecular space (P < 0.001). In conclusion, our results demonstrate that bee pollen (1.0%, 10 g/kg of feed) supplementation caused significant negative effects on the mechanical endurance of the tibia of quails, while showed beneficial effects on trabecular bone histomorphometry.